Strengthening Monitoring and Evaluation of HIV/AIDS Components in Road Projects - World Bank (World Bank, 2012)
This report aims to strengthen the monitoring and evaluation (M&E) aspects of HIV/AIDS components in road projects. Result-based M&E helps decision makers assess whether and how goals are being achieved over time, while at the same time identify problems that need to be tackled. The report assesses the extent of M&E in current HIV/AIDS components in the portfolio of road projects financed by the World Bank. It provides an overview of work to date to identify core indicators for measuring results of HIV and AIDS prevention, specifically focusing on the monitoring of results of transport related activities, proposing a menu of HIV and AIDS indicators and a sample results framework.